2004
DOI: 10.1176/jnp.16.3.330
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana Use and Cognitive Function in HIV-Infected People

Abstract: The effect of marijuana use on cognitive function is controversial. Although marijuana use is common in HIV-infected individuals for recreational and medicinal purposes, there have been no studies of the impact of marijuana on cognitive function in these subjects. Marijuana also has known immunologic effects, which increases the relevance in HIV-infected patients. We examined the interaction of HIV disease-stage and marijuana use in 282 subjects, stratified by disease stage and frequency of marijuana use. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 25 publications
3
34
2
Order By: Relevance
“…Neurological testing, intelligence, depression and anxiety were measured in 288 individuals (74 HIV seronegative, 127 HIVseropositive-asymptomatic and 87 HIV-seropositivesymptomatic). Marijuana use was dichotomized: those who reported having used less than once per month over the previous year were categorized as a no/minimal-use group with the remaining persons categorized as a frequent-use group [71] . Results revealed a significant interaction effect for HIV disease and marijuana use with respect to overall impairment score-the difference between the no/minimal-use group and frequent-use group was greatest among subjects with symptomatic HIV infection.…”
Section: Marijuanamentioning
confidence: 99%
“…Neurological testing, intelligence, depression and anxiety were measured in 288 individuals (74 HIV seronegative, 127 HIVseropositive-asymptomatic and 87 HIV-seropositivesymptomatic). Marijuana use was dichotomized: those who reported having used less than once per month over the previous year were categorized as a no/minimal-use group with the remaining persons categorized as a frequent-use group [71] . Results revealed a significant interaction effect for HIV disease and marijuana use with respect to overall impairment score-the difference between the no/minimal-use group and frequent-use group was greatest among subjects with symptomatic HIV infection.…”
Section: Marijuanamentioning
confidence: 99%
“…A meta-analysis (78) of the residual neurocognitive effects of cannabis use reported decreases in the performance of memory tasks. A recent study (79) suggested that patients with advanced HIV/AIDS may be at risk for aggravated memory impairment due to cannabis use. The long-term effects of cannabis use on neurocognitive function may be due to a direct effect of cannabis use or may be due to confounding effects (80); further research is required to draw conclusions.…”
Section: Long-term Effects Dependencymentioning
confidence: 99%
“…Cristiani et al [97] did find poorer performance on memory tasks for daily cannabis users with symptomatic HIV as compared with those with asymptomatic HIV and a sero-negative control group, and the amount of impairment appeared to increase across the stages of HIV disease. The authors concluded that cannabis affected users more as the HIV disease progressed; they postulated that subtle effects may become more significant in an immune-compromised person.…”
Section: Cannabismentioning
confidence: 94%